H2S Prodrug, SG-1002, Protects against Myocardial Oxidative Damage and Hypertrophy In Vitro via Induction of Cystathionine β-Synthase and Antioxidant Proteins - Rahib K. Islam; Erinn Donnelly; Erminia Donnarumma; Fokhrul Hossain; Jason D. Gardner; Kazi N. Islam (Biomedicines)
Endogenously produced hydrogen sulfide (H2S) is critical for cardiovascular homeostasis. Therapeutic strategies aimed at increasing H2S levels have proven cardioprotective in models of acute myocardial infarction (MI) and heart failure (HF). The present study was undertaken to investigate the effects of a novel H2S prodrug, SG-1002, on stress induced hypertrophic signaling in murine HL-1 cardiac muscle cells. Treatment of HL-1 cells with SG-1002 under serum starvation without or with H2O2 increased the levels of H2S, H2S producing enzyme, and cystathionine β-synthase (CBS), as well as antioxidant protein levels, such as super oxide dismutase1 (SOD1) and catalase, and additionally decreased oxidative stress. SG-1002 also decreased the expression of hypertrophic/HF protein markers such as atrial natriuretic peptide (ANP), brain natriuretic peptide (BNP), galectin-3, TIMP1, collagen type III, and TGF-β1 in stressed HL-1 cells. Treatment with SG-1002 caused a significant induction of cell viability and a marked reduction of cellular cytotoxicity in HL-1 cells under serum starvation incubated without or with H2O2. Experimental results of this study suggest that SG-1002 attenuates myocardial cellular oxidative damage and/or hypertrophic signaling via increasing H2S levels or H2S producing enzymes, CBS, and antioxidant proteins.